1, 3, 4-Thiadiazoles and 1, 3-thiazoles from one-pot reaction of bisthioureas with 2-(bis(methylthio)methylene)malononitrile and ethyl 2-cyano-3, 3-bis(methylthio)acrylate. (2nd January 2017) - Aly, Ashraf A.; Hassan, Alaa A.; Bräse, Stefan; Ibrahim, Mahmoud A. A.; Abd Al-Latif, El-Shimaa S. M.; Spuling, Eduard; Nieger, Martin
ABSTRACT: Bisthioureas reacted with either 2-(bis(methylthio)methylene)malononitrile or ethyl 2-cyano-3, 3-bis(methylthio)acrylate to give 1, 3, 4-thiadiazoles and 1, 3-thiazoles. Only, the reactive allyl derivative of bisthioureas reacted with the bis(methylthio)methylene compounds to give 1, 3-thiazoles. The mechanism was discussed. The structures of products were proved by MS, IR, NMR and elemental analyses and X-ray structure analysis. GRAPHICAL ABSTRACT: